Market leverage of real estate firms in India: empirical study - Dinabandhu Bag (Proceedings of the 7th International Business Research Conference at Indian Education Society, Mumbai, August 2014, 2014)
Growing urbanization, increasing population and increased per capita income have boosted the demand for housing in India. This empirical study gives us an explanation of how the market leverage of the real state firms in India are affected by firm specific attributes and external market or macroeconomic factors. Property financing is known as infrastructure financing where there exits the problems of longer gestation period, less predictable cash flows and challenge of accessing capital. This paper compares the property firms from other firms to differentiate their financial characteristics. It analyses the determinants of the market leverage for a sample of 40 Indian listed property companies for 8 year period from 2005 to 2012 and shows that current market leverage is positively and significantly impacted by previous leverage and also fewer firm characteristics that include contemporaneous operational efficiency, growth option, and change in working capital, cost of funds, etc. We conclude that transparency in property markets and accuracy in financial disclosure can help property firms` access capital and maintain their leverage. We also emphasize that the recent guidelines of SEBI on the introduction of REITs (Real Estate Investment Trusts) and real estate funds (REFs) are policy initiatives to channelize funds for this sector.
Keywords: G10; G12; 330; Leverage Ratio; Profitability; Growth; Exchange Rate